VIRTUAL REALITY IN ENGLISH LANGUAGE EDUCATION: ENHANCING IMMERSIVE LANGUAGE LEARNING ENVIRONMENTS - Juchkov , Maxim (Effective scientific journals, 2026)
The integration of emerging digital technologies in education has significantly transformed language learning methodologies. Among these technologies, Virtual Reality (VR) has gained increasing attention due to its ability to create immersive and interactive learning environments. This study examines the role of Virtual Reality in enhancing English language learning, particularly in improving learners’ communicative competence, engagement, and contextual language acquisition. The research employs a mixed-method approach involving experimental classroom implementation and learner perception analysis. Data were collected from university-level English as a Foreign Language (EFL) students through pre- and post-tests, classroom observations, and questionnaires. The results indicate that VR-based learning environments significantly improve speaking fluency, listening comprehension, and learner motivation. The findings suggest that immersive VR scenarios allow learners to practice authentic communication in simulated real-life contexts, thereby reducing language anxiety and promoting experiential learning. The study contributes to contemporary language education research by proposing a pedagogical framework for integrating VR technology into English language teaching.